Application of solid-phase microextraction for the analysis of polycyclic aromatic hydrocarbons in hyophila involuta as a natural biosensor / Elizabeth Fong Yew Mei - Fong, Elizabeth Yew Mei (2010)
This work describes a simple and rapid extraction method by using solid-phase microextraction (SPME) technique for the determination of polycyclic aromatic hydrocarbons (PAHs) from mosses of Hyophila involuta which is found commonly and abundantly throughout Peninsular Malaysia. Mosses have been chosen in our study since they are effective bioindicators as they take up nutrients and pollutants directly from the atmosphere and they have no root system. These properties make them ideal for evaluating pollutant levels in the air over a monitored period of time. This study has been developed and optimized based on the extraction of the analytes of interest from the headspace over the moss samples with SPME followed by the analysis by gas chromatography-flame ionization detector (GC-FID). Factors affecting the SPME method, such as extraction mode and effects of the addition of chemical modifiers were evaluated, and the precision, linearity and detection limits were validated. Extraction was performed using operating conditions with standard addition method using 100 μm poly(dimethylsiloxane) (PDMS) fiber under the following conditions: extraction temperature of 150 ºC, extraction time of 90 min, desorption time and temperature of 15 min and 275 ºC, respectively, with the addition of 250 μl of 5% (w/v) NaCl salt solution. The headspace SPME method was developed using non-spiked and spiked moss samples in a concentration range of 0-2600 ng/g. The method showed good linearity for the tested concentration range with regression coefficient ranging between 0.9721 and 0.9974. The relative standard deviations which were determined at the low (150 ng/g), mid (2000 ng/g) and high (2600 ng/g) concentrations for all PAHs were between 2-37%, except for some compounds (benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(a)pyrene, and indeno(123-cd)pyrene) which exhibited slightly higher values (42-69%). Recoveries were in relatively high levels for all compounds at three different concentration levels, and ranged from 80-119% except for a few compounds (benzo(k)fluoranthene, indeno(123-cd)pyrene, dibenzo(ah)anthracene, and benzo(ghi)perylene) which showed lower recoveries (23-67%) at concentration level of 150 ng/g. The detection and quantification limits were 1.3-193.1 pg/g and 4.2-643.6 pg/g, respectively for all PAH compounds studied. The developed method was then applied for the quantification of PAH compounds with heavy traffic pollution from contaminated moss samples collected from selected stations in the Klang Valley area.